Intravitreal Dexamethasone Implant as a Sustained Release Drug Delivery Device for the Treatment of Ocular Diseases: A Comprehensive Review of the Literature - Claudio Iovino; Rodolfo Mastropasqua; Marco Lupidi; Daniela Bacherini; Marco Pellegrini; Federico Bernabei; Enrico Borrelli; Riccardo Sacconi; Adriano Carnevali; Rossella D'Aloisio; Alessio Cerquaglia; Lucia Finocchio; et al. (MDPI AG, 2020)
Drug delivery into the vitreous chamber remains a great challenge in the pharmaceutical industry due to the complex anatomy and physiology of the eye. Intravitreal injection is the mainstream route of drug administration to the posterior segment of the eye. The purpose of this review is to assess the current literature about the widening use of the intravitreal 0.7 mg dexamethasone (Dex) implant, and to provide a comprehensive collection of all the ocular disorders that benefit from Dex administration. Although anti-vascular endothelial growth-factors (VEGFs) have been largely indicated as a first-choice level, the Dex implant represents an important treatment option, especially in selected cases, such as vitrectomized eyes or patients in whom anti-VEGF failed or are contraindicated. In this article, the safety profile as well as the list of the possible complications related to intravitreal Dex injection are also discussed.